The Role of Electronic Word of Mouth In Improving Brand Image of Online Shop - Sri Vandayuli Riorini, Christina Catur Widayati (Jurnal Manajemen, 2019)
Brand image is a strategy that is widely utilized by companies to win the competition. To identify the factors that influence the brand image of online store, empirical study was conducted to analyze the direct influence of electronic customer satisfaction, electronic word of mouth toward the brand image of online store, and to analyze the indirect effect of electronic customer satisfaction toward the brand image of online store through electronic word of mouth. Data were collected from 200 online store consumers and analyzed by Structural Equation Modeling method. From the results of processing data to test the proposed hypothesis, it is known that to improve the brand image of online stores, the online store manager should focus on how to boost the number of consumers who will provide reviews about online stores or push electronic word of mouth. Â